LOCAL WISDOM AND VALUE OF CHARACTER IN LEVEL OF AJI KRAMA AT SASAK WEDDING TRADITION - Agusman Agusman; Imam Suyitno; Yuni Pratiwi (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
The discourse of marriage tradition when viewed based on a theoretical point of view will result in a form of concepts, meanings, and functions. In this case, the discourse of the tradition in question is the discourse of the sorong serah aji krama tradition. The discourse of this tradition is found in the Lombok-Sasak area located in Jonggat Subdistrict, Central Lombok District, West Nusa Tenggara Province (NTB). The axes of aji krama contained in this area have levels ranging from the bottom of the so-called 33, 66, and 100. In this case, the study is to find the value contained in the level aji krama is also explained to the community that in the level of aji krama is not only limited to discourse or celebration in a mere cultural symbol, but contains the value of philosophical life. In this case, the method used in collecting data is an interview with a prominent traditional figure who knows the ins and outs of the tradition of handling the aji krama well. Thus, the data in this study is verbal aspect in the form of interviews related to the level of aji krama contained in the area. Data analysis in this case uses Hermeneutic’s Ricoeur's thinking framework that sees a text of three levels, namely semantic level, philosophical level, and level of existence. Based on the results of this study, thrust of aji krama as a tradition of marriage which also has aji aji krama level has a strong philosophical foundation. It can be seen from the level of aji 33 which shows an understanding of self, God, and all his power obtained through understanding the nature of Allah SWT. Aji 66 is a multilevel of understanding aji 33 approaching to the category of human being (rodiallah) and aji 100 is the highest category to the understanding of the nature of self and God and all forms of his power gained from a deep understanding of the 99 ulma asthma that leads to one form, that is Allah SWT. Thus, the understanding is a category of local wisdom that contains the value of character and is represented in the form of religious character.